Method for producing a material having an organically modified carbon surface and the material

By using supercritical water or organic solvents for surface oxidation and organic modification of carbon materials, the method achieves uniform and effective organic modification, addressing the challenges of aggregation and impaired function in existing technologies.

JP7655559B2Active Publication Date: 2025-04-02SUPER NANO DESIGN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022146708
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-04-02
Estimated Expiration
2035-10-22

AI Technical Summary

Technical Problem

Existing methods for modifying carbon nanotubes and other carbon materials face challenges in achieving uniform organic modification at sufficient concentrations, often resulting in aggregation and impaired function.

Method used

The method involves surface oxidation of carbon materials using supercritical water or supercritical organic solvents, followed by organic modification using organic compounds with functional groups, to achieve uniform modification and prevent aggregation.

Benefits of technology

This approach allows for uniform organic modification of carbon surfaces at high concentrations, preventing aggregation and enhancing the functional properties of carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655559000002
    Figure 0007655559000002
  • Figure 0007655559000003
    Figure 0007655559000003
  • Figure 0007655559000004
    Figure 0007655559000004
Patent Text Reader

Abstract

The present invention provides a method for uniformly and organically modifying the carbon surface of a material at a sufficient concentration, and a material whose carbon surface has been organically modified. [Solution] This method includes a surface oxidation step in which the carbon surface of a material is oxidized with an oxidizing agent, and an organic modification step in which, after the surface oxidation step, an organic compound (excluding silicon compounds) having one or more functional groups and a solvent is added to the surface-oxidized material from which the solvent and oxidizing agent used in the surface oxidation step have been removed or diluted, and the surface-oxidized surface is organically modified with the organic compound in subcritical water, supercritical water, or supercritical organic solvent as a reaction field.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a material having an organically modified carbon surface, and to the material. [Background technology]

[0002] Carbon materials such as carbon nanotubes (CNTs), fullerenes, graphene, carbon black, nanodiamonds, and carbon fibers require good dispersion in solvents and polymers to demonstrate their functions. However, it is difficult to control the affinity, and they tend to aggregate, preventing them from demonstrating their original functions, which has greatly hindered the application and development of these nanocarbon materials.

[0003] In order to suppress such aggregation, it is sufficient to modify the carbon material with organic molecules, but unlike inorganic materials (hydroxyl groups), carbon materials do not have adsorption and binding sites for organic molecules, so good modification is not always possible. Therefore, as a method for highly efficient organic modification, a method has been developed in which carbon nanotubes are reacted with an organometallic compound to obtain an organically modified carbon nanotube reduced product, and then this organically modified carbon nanotube reduced product is reacted with an organosilicon halogen compound to obtain an organically modified carbon nanotube (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4948676 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the method described in Patent Document 1, carbon nanotubes are dispersed in an organic solvent at a temperature below room temperature, and then an organometallic compound is added to the solvent to react with the carbon nanotubes. There was a problem that the carbon nanotubes aggregated at the dispersion stage, resulting in modification at an extremely low concentration or modification on the aggregates.

[0006] The present invention has been made in light of these problems, and has an object to provide a method capable of uniformly organically modifying the carbon surface of a material at a sufficient concentration, and a material whose carbon surface has been organically modified. [Means for solving the problem]

[0007] In order to achieve the above object, the present inventor has come up with the present invention through the following considerations. That is, in order to modify a carbon material well, it is important to modify the surface of the carbon material, and if hydroxyl groups, aldehydes, carboxylic acids, etc. are generated, organic modification can be carried out starting from these. Therefore, oxidation treatment of the surface of the carbon material has been conventionally carried out using oxygen, ozone, hydrogen peroxide, sulfuric acid, nitric acid, etc. as an oxidizing agent. In addition, plasma treatment is also carried out to increase the effectiveness of the treatment.

[0008] However, oxidation in the gas phase had the problem that only the surface of the aggregates was oxidized. In addition, there was also the problem that a sufficient surface oxide concentration was not necessarily obtained because oxides (CO, CO2) were simultaneously desorbed. In contrast, when oxidation was performed in water at a lower temperature, the carbon material had a low affinity, causing phase separation from the water. In addition, aggregates were formed and either precipitated or floated on the surface of the water. For this reason, there was also the problem that modification with sulfuric acid, nitric acid, or hydrogen peroxide only treated the surfaces of the aggregates and suspended matter.

[0009] In response to such problems, the present inventors have conceived the idea that carbon materials can be dispersed well by utilizing supercritical water, since the dielectric constant of supercritical water is low, at about 2 to 10, and the water also exhibits the properties of an organic solvent.

[0010] In general, the oxidation reaction of carbon consists of the formation of surface oxides in the following reactions (1) and (3) and the elimination of oxides in the following reactions (2) and (4). (1) C+O2= C(O)(O) (2) C(O)(O) = CO + (O) (3) C+H2O(CO2) =C(O)+H2(CO) (4) C(O)=CO

[0011] In general, the activation energies of reactions (2) and (4) are higher than those of reactions (1) and (3), with reaction (4) being the highest. Since these are consecutive reactions, it is well known that the lower the temperature, the more the elimination reactions of (2) and (4) become rate-determining.

[0012] When the objective is to oxidize the surface of carbon, it is important to set conditions that increase the concentration of C(O). For this purpose, the oxidation reactions (3) and (4) by water vapor are desirable, and in particular, to increase the concentration of C(O), it is desirable to promote the reaction (3) and make the reaction (4) the rate-limiting condition. In other words, it is desirable to have low temperatures and high H2O partial pressures. This has been experimentally confirmed, although it is a gas-phase reaction at 800-1000°C and several tens of atmospheres (Takao Nozaki, Tadafumi Adschiri and Kaoru Fujimoto, Energy & Fuels, 1991 5(4), pp.610-611).

[0013] According to the oxidation reaction mechanisms of (3) and (4), the concentration of C(O) is C(O)=number of active points / (1+K H2O) K=k3 / k4 (k3 is the rate constant for reaction (3), and k4 is the rate constant for reaction (4)) From this equation, it can be expected that by increasing the pressure, a higher concentration of C(O) will be produced.

[0014] On the other hand, it has been reported that carbon can be gasified by creating a supercritical state at 600-650°C and 25.5-34.5 MPa (Y. Matsumura, X, Xu and MJ Antal, Jr, Carbon Vol.35, No.6, pp.819-824), and it has been shown that reaction (4) also occurs under these conditions. The present inventors considered that in order to suppress the elimination of C(O) in (4), a lower temperature is desirable, and that subcritical or supercritical hydrothermal conditions at 200-500°C or oxidation treatment in a supercritical organic solvent are desirable.

[0015] Next, we will consider organic modification of the carbon material surface. Methods for organic modification include dehydration reactions such as ether and ester generation and acid-amide reactions, as well as Friedel-Crafts and Diels-Alder reactions. However, since the carbon material after surface treatment by oxidation has hydrophilic groups, it does not disperse in organic solvents and forms aggregates, and there is a problem that organic modification occurs on the aggregates. In addition, there is a problem that long-chain organic molecules disperse in water but do not dissolve in water, resulting in phase separation. In addition, there is also a problem that dehydration reactions cannot proceed efficiently in terms of equilibrium and kinetics.

[0016] In response to these problems, the present inventors have come up with the idea that by using a supercritical water reaction field or a supercritical organic solvent reaction field, it is possible to form a homogeneous phase with any organic molecule, and that hydrophilically treated carbon materials can also be well dispersed. They have also come up with the idea that in such high-temperature reaction fields, the exothermic dehydration reaction shifts to the progress side. Furthermore, they have also come up with the idea that in a supercritical field or a supercritical organic solvent reaction field, these organic molecules and carbon materials form a well-dispersed homogeneous phase, but have a high chemical potential, so that the reaction equilibrium shifts to the product side, and a high kinetic rate can be obtained.

[0017] Next, we will consider a surface modification method that does not involve oxygen surface treatment. The above-mentioned oxidation and organic modification treatments can significantly impair the inherent functions and physical properties of carbon materials. For example, single-walled CNTs (single-walled carbon nanotubes), graphene, and fullerenes are single carbon layers, and their developed structures can be destroyed by etching or oxidizing them. In addition, the inclusion of oxygen and the binding of an organic modifier create a new electronic state, which can significantly change the physical properties of the carbon material.

[0018] Therefore, as a surface modification method that does not require oxygen surface treatment, we consider the Diels Alder reaction, which forms carbon-carbon bonds, and π-π interactions with aromatic carbon. Advanced aromatics that can be used in these reactions include benzene, naphthalene, anthracene, and organically modified graphene flakes. However, because of the high affinity between organic solvents and these modifiers, there is a problem that sufficient adsorption may not be obtained even if these are adsorbed in an organic solvent. In addition, there is also a problem that these modifiers may be desorbed by washing. In addition, there is a problem that the reactivity of the Diels Alder reaction with the nanomaterial surface in an organic solvent is extremely low compared to reactions with normal molecules.

[0019] In response to such problems, the inventors have conceived that since subcritical water, supercritical water, and supercritical organic solvents have low dielectric constants, by using them as solvents, it is possible to form a homogeneous phase with any organic molecule, and carbon materials can also be well dispersed. In addition, the inventors have conceived that in a supercritical field or a reaction field of a supercritical organic solvent, these organic molecules and carbon materials have high chemical potential, the reaction equilibrium shifts to the product side, and a high kinetic rate can be obtained. In addition, the inventors have conceived that not only adsorption and π-π interaction formation, but also Diels Alder reactions have high chemical potential, and the reaction is promoted.

[0020] Through the above considerations, the present inventors arrived at the present invention. That is, the manufacturing method according to the present invention includes a surface oxidation step of oxidizing the carbon surface of a material with an oxidizing agent, and an organic modification step of adding an organic compound having one or more functional groups (excluding silicon compounds) and a solvent to the surface-oxidized material, from which the solvent used in the surface oxidation step and the oxidizing agent have been removed or diluted, and organically modifying the surface-oxidized surface with the organic compound in subcritical water, supercritical water, or supercritical organic solvent as a reaction field. The method for producing an organically modified carbon material according to the present embodiment is characterized in that the surface of a carbon material is organically modified with an organic compound (excluding silicon compounds) having one or more functional groups in a reaction field of subcritical water, supercritical water, or a supercritical organic solvent. Preferably, the method for producing an organically modified carbon material according to the present invention organically modifies the surface of the carbon material by reacting the organic compound with the carbon material or by interaction between the organic compound and the surface of the carbon material.

[0021] In the method for producing an organically modified carbon material according to the present embodiment, any organic molecule can form a homogeneous phase by using subcritical water, supercritical water, or a supercritical organic solvent as a reaction field, and the carbon material or the carbon material that has been surface-treated (hydrophilized) by oxidation can be well dispersed without agglomeration. Therefore, the surface of the carbon material can be uniformly organically modified at a sufficient concentration by carbon-carbon bonds by Diels Alder reaction or π-π interactions with aromatic carbon. In addition, even when the carbon material is oxidized before organic modification, the surface of the carbon material can be uniformly oxidized at a sufficient concentration. Furthermore, the surface of the carbon material that has been surface-treated by oxidation can also be uniformly organically modified at a sufficient concentration by ether bonds, ester bonds, amino bonds, amide bonds, etc. in the reaction field of subcritical water, supercritical water, or a supercritical organic solvent.

[0022] The supercritical organic solvent is an organic solvent that is kept at a temperature and pressure equal to or higher than the critical point. The organic solvent may be any organic solvent that can be used, such as hexane, ethanol, or toluene.

[0023] In the method for producing an organically modified carbon material according to the present embodiment, the carbon material may be oxidized and then organically modified with the organic compound. Alternatively, the carbon material may be oxidized and organically modified with the organic compound in the reaction field. In this case, C(O) is generated at a high concentration, and then organic modification is performed with high reaction efficiency, so that a carbon material that is organically modified at a high concentration can be obtained.

[0024] In the method for producing an organically modified carbon material according to the present embodiment, the carbon material may be oxidized with oxygen released from subcritical water or supercritical water in a reaction field. Alternatively, the carbon material may be oxidized with an oxidizing agent containing at least one of hydrogen peroxide, oxygen gas, nitric acid, and sulfuric acid in a reaction field in subcritical water, supercritical water, or supercritical organic solvent. In this case, the supercritical water or supercritical organic solvent and the oxygen gas form a homogeneous phase, and the chemical potential (oxidation activity) of the gas itself can be raised to an extremely high level, so that the surface of the carbon material can be effectively oxidized uniformly at a sufficient concentration. In particular, when hydrogen peroxide is used in supercritical water, the radical network rotates at a high speed, and higher oxidation activity can be obtained.

[0025] It is known that the gasification reaction of carbon occurs from the edges of the graphene structure. In addition, the oxidation reaction by H2O also mainly occurs from the edges. However, in basic research into carbon gasification, it has been found that the graphene surface can also be etched using oxygen. For this reason, by performing an etching process using oxygen (or hydrogen peroxide) in supercritical water, it is possible to improve the C(O) concentration by supercritical water oxidation. It is also believed that the same effect can be obtained with oxygen gas, nitric acid, sulfuric acid, etc. This allows the surface of the carbon material to be effectively oxidized at a sufficient concentration.

[0026] In the method for producing an organically modified carbon material according to the present embodiment, it is preferable to perform freeze-drying or supercritical treatment after organically modifying the surface of the carbon material, and then recover the organically modified carbon material. When organic modification is performed using subcritical water or supercritical water, the carbon material after organic modification is hydrophobic, so it automatically phase separates from the water. For this reason, it can be recovered well by adding a small amount of organic solvent. However, when an organic solvent is used during organic modification, it is necessary to dry and remove the solvent, and the capillary force acts in the drying process, causing the carbon material to aggregate. Therefore, by performing freeze-drying or supercritical treatment, the capillary force can be suppressed to prevent aggregation, and the organically modified carbon material can be recovered with high efficiency. In particular, by performing supercritical carbon dioxide drying, the organic solvent can be completely recovered and reused. It is also possible to separate it from the unused modifier.

[0027] In the method for producing an organically modified carbon material according to the present embodiment, the carbon material preferably contains at least one of amorphous carbon, carbon nanotubes, graphene, graphite, nanodiamond, diamond-like carbon, fullerene, carbon fiber, and these materials containing one or more of N, S, P, B, and O. In this case, the surfaces of these carbon materials can be organically modified uniformly at a sufficient concentration.

[0028] In the method for producing an organically modified carbon material according to the present embodiment, the carbon material is preferably organically modified with the organic compound by an ether bond, an ester bond, a bond via an N atom including an amino bond or an amide bond, a bond via an S atom, a bond via a P atom, a bond via a B atom, a phosphate ester bond, a borate ester bond, a phosphorous acid bond, a phosphonic acid bond, a phosphonous acid bond, a phosphinic acid bond, a phosphine acid bond, a phosphine acid bond, a carbon-carbon bond, or a π-π interaction. In this case, the surface of each carbon material can be effectively organically modified by selecting an optimal bonding method according to the type of carbon material to be organically modified. For example, when the carbon material includes at least one of carbon nanotubes, graphene, graphite, and fullerene, it is preferable to organically modify the surface of the carbon material with an aromatic compound as an organic compound by π-π interaction.

[0029] In the method for producing an organically modified carbon material according to the present embodiment, the temperature of the reaction field is preferably 200° C. or more and less than 450° C. The pressure of the reaction field is preferably 20 MPa or more and 40 MPa or less. In this case, the surface of the carbon material can be organically modified particularly effectively.

[0030] The organically modified carbon material according to this embodiment is characterized in that the surface of a carbon material is organically modified with an organic compound (excluding silicon compounds), and the weight ratio of the molecules that organically modify the surface of the carbon material is 2 wt.% or more. Since the organically modified carbon material according to this embodiment is formed by organically modifying the surface of a carbon material at a weight ratio of 2 wt.% or more, it disperses well without agglomeration even in a solvent or polymer. This allows the function of the carbon material to be fully exhibited. The organically modified carbon material according to this embodiment can be suitably produced by the method for producing an organically modified carbon material according to the present invention.

[0031] In the organically modified carbon material according to the present embodiment, the carbon material preferably includes at least one of amorphous carbon, carbon nanotubes, graphene, graphite, nanodiamond, diamond-like carbon, fullerene, carbon fiber, and materials containing one or more of N, S, P, B, and O in these materials. In addition, the carbon material is preferably organically modified with the organic compound by, for example, an ether bond, an ester bond, an amino bond, a bond via an N atom including an amide bond, a bond via an S atom, a bond via a P atom, a phosphate ester bond, a phosphorous bond, a phosphonic acid bond, a phosphonous acid bond, a phosphinic acid bond, a phosphine acid bond, a carbon-carbon bond, or a π-π interaction, depending on the type of the carbon material, so as to be effectively organically modified. Effect of the Invention

[0032] According to the present invention, it is possible to provide a method for uniformly and organically modifying the carbon surface of a material at a sufficient concentration, and a material having an organically modified carbon surface. [Brief description of the drawings]

[0033] [Figure 1] 1 is a graph showing (a) the results of thermogravimetric analysis and (b) the FTIR spectrum after surface oxidation treatment of nanodiamond under hydrothermal conditions according to an embodiment of the present invention, in accordance with a method for producing an organically modified carbon material. [Diagram 2] 1 is a graph showing FTIR spectra when multi-walled carbon nanotubes are subjected to surface oxidation treatment with hydrogen peroxide solution having a concentration of (a) 3% and (b) 6% under hydrothermal conditions according to a method for producing an organically modified carbon material according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after surface oxidation treatment under hydrothermal conditions according to a method for producing an organically modified carbon material according to an embodiment of the present invention. [Figure 4] 1 is a graph showing the results of thermogravimetric analysis after a surface oxidation treatment of graphene under hydrothermal conditions according to a manufacturing method of an organically modified carbon material according to an embodiment of the present invention. [Diagram 5] 1 is a graph showing FTIR spectra for each reaction temperature after reaction of multi-walled carbon nanotubes with hexylamine under hydrothermal conditions according to a method for producing an organically modified carbon material according to an embodiment of the present invention. [Figure 6] FIG. 11 is a graph showing FTIR spectra after reaction of multi-walled carbon nanotubes with hexylamine under hydrothermal conditions according to the embodiment of the present invention, when the pH of the solvent water is (a) 9.8, (b) 10.6, and (c) 11.3. [Figure 7] 4 is a graph showing FTIR spectra after reaction of multi-walled carbon nanotubes with hexylamine in an organic solvent according to the embodiment of the present invention, when the solvent is (a) toluene and (b) ethanol. [Figure 8] 1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with hexylamine, decylamine, dodecylamine, and oleylamine under hydrothermal conditions according to the embodiment of the present invention, in accordance with the method for producing an organically modified carbon material. [Figure 9] FIG. 1 is a graph showing FTIR spectra of multi-walled carbon nanotubes after reaction with (a) hexylamine, (b) decylamine, and (c) dodecylamine at 350° C. under hydrothermal conditions, according to a method for producing an organically modified carbon material according to an embodiment of the present invention, and FTIR spectra after reaction with (d) hexylamine, (e) decylamine, and (f) dodecylamine at 400° C. [Figure 10] 1A-1D are micrographs of multi-walled carbon nanotubes after reaction with (a) hexylamine, (b) and (c) decylamine, and (d) dodecylamine under hydrothermal conditions according to an embodiment of the present invention for producing an organically modified carbon material. [Figure 11] 1A is a graph showing (a) the thermogravimetric analysis results, (b) the FTIR spectrum, and (c) an enlarged FTIR spectrum of (b) after the reaction of multi-walled carbon nanotubes with aspartic acid under hydrothermal conditions according to a manufacturing method of an organically modified carbon material according to an embodiment of the present invention. [Figure 12]4 is a graph showing (a) the thermogravimetric analysis result and (b) the FTIR spectrum after the reaction of multi-walled carbon nanotubes with 1-decanol under hydrothermal conditions according to the embodiment of the present invention. FIG. [Figure 13] FIG. 13 is a graph showing (a) the results of thermogravimetric analysis with and without water during the reaction, (b) the FTIR spectrum when reacted in water, (c) an FTIR spectrum of an enlarged portion of (b), (d) the FTIR spectrum when no t-BuOH is present, (e) an FTIR spectrum of an enlarged portion of (d), (f) the FTIR spectrum when reacted without water, and (g) an FTIR spectrum of an enlarged portion of (f), after the reaction of multi-walled carbon nanotubes with t-BuOH by the manufacturing method of an organically modified carbon material according to an embodiment of the present invention. [Figure 14] FIG. 1 is a graph showing (a) the thermogravimetric analysis results and (b) the FTIR spectra of oxidized and non-oxidized multi-walled carbon nanotubes after reaction with t-BuOH according to a method for producing an organically modified carbon material according to an embodiment of the present invention. [Figure 15] 1A is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with t-BuOH in sulfuric acid according to a method for producing an organically modified carbon material according to an embodiment of the present invention, and FIG. 1B is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with t-BuOH in sulfuric acid, and FIG. [Figure 16] FIG. 13 is a graph showing (a) the thermogravimetric analysis results when multi-walled carbon nanotubes are reacted with t-BuOH in sulfuric acid and then immersed in hexane for 24 hours and 70 hours according to a method for producing an organically modified carbon material according to an embodiment of the present invention, (b) an FTIR spectrum after immersion for 24 hours, and (c) an FTIR spectrum after immersion for 70 hours. [Figure 17] 1 is a graph showing the results of thermogravimetric analysis after reaction of BMAB with decylamine under hydrothermal conditions according to an embodiment of the present invention. [Figure 18]FIG. 1 is a graph showing (a) the results of thermogravimetric analysis after BMAB is surface-oxidized in supercritical water and then reacted with decylamine in an organic solvent, (b) an FTIR spectrum of BMAB after surface-oxidized in supercritical water, and (c) an FTIR spectrum of BMAB after reaction with decylamine in hexane, according to a manufacturing method of an organically modified carbon material according to an embodiment of the present invention. [Figure 19] FIG. 1 is a graph showing (a) the results of thermogravimetric analysis after BMAB is surface-oxidized with nitric acid and then reacted with decylamine in an organic solvent according to an embodiment of the present invention, and (b) FTIR spectra when reacted in ethanol, (c) hexane, and (d) toluene. [Figure 20] Graphs showing (a) thermogravimetric analysis results, (b) FTIR spectrum, and (c) FTIR spectrum after further treatment with oleylamine of multi-walled carbon nanotubes after reaction with NBS under hydrothermal conditions according to an embodiment of the present invention, using a method for producing an organically modified carbon material. [Figure 21] 1 is a graph showing the results of EDX analysis of (a) multi-walled carbon nanotubes after reaction with NBS under hydrothermal conditions and (b) untreated multi-walled carbon nanotubes according to an embodiment of the present invention. [Figure 22] 4A and 4B are micrographs of multi-walled carbon nanotubes after reaction with NBS under hydrothermal conditions at (a) 200° C. and (b) 250° C. according to an embodiment of the present invention for producing an organically modified carbon material. [Figure 23] FIG. 1 is a graph showing the results of thermogravimetric analysis of (a) multi-walled carbon nanotubes, (b) graphene, and (c) single-walled carbon nanotubes after reaction with DMBD under hydrothermal conditions according to an embodiment of the present invention, in accordance with a method for producing an organically modified carbon material. [Figure 24] 1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with DMBD in an organic solvent according to an embodiment of the present invention. [Diagram 25] FIG. 25 is a graph showing the change in the weight loss rate of FIG. 23(a) and FIG. 24 with respect to reaction time. [Figure 26] 1 is a graph showing the results of thermogravimetric analysis of single-walled carbon nanotubes after reaction with DMBD under hydrothermal conditions according to an embodiment of the present invention, in accordance with a method for producing an organically modified carbon material. [Figure 27] 4 is a graph showing (a) the thermogravimetric analysis result and (b) the FTIR spectrum after the reaction of multi-walled carbon nanotubes with anthracene under hydrothermal conditions according to the embodiment of the present invention. [Figure 28] 1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with anthracene under hydrothermal conditions and in an organic solvent according to an embodiment of the present invention. [Figure 29] FIG. 1A is a graph showing (a) the thermogravimetric analysis results after reaction of multi-walled carbon nanotubes with aminoanthracene under hydrothermal conditions according to a method for producing an organically modified carbon material according to an embodiment of the present invention, and FTIR spectra at reaction temperatures of (b) 200° C., (c) 250° C., (d) 300° C., and (e) 350° C. [Diagram 30] 1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with aminoanthracene in an organic solvent according to an embodiment of the present invention. [Diagram 31] 4 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with naphthalene under hydrothermal conditions according to the embodiment of the method for producing an organically modified carbon material of the present invention. [Diagram 32] 1A is a graph showing (a) the results of thermogravimetric analysis after reaction of multi-walled carbon nanotubes with benzyl alcohol under hydrothermal conditions according to a method for producing an organically modified carbon material according to an embodiment of the present invention, and (b) the relationship between the weight change rate and the reaction temperature. [Diagram 33] FIG. 1 shows (a) an FTIR spectrum, (b) a graph showing an enlarged portion of (a) of the FTIR spectrum, and (c) and (d) micrographs of multi-walled carbon nanotubes after reaction with benzyl alcohol under hydrothermal conditions according to an embodiment of the present invention. [Diagram 34]1 is a graph showing the results of thermogravimetric analysis of multi-walled carbon nanotubes after reaction with NDCA under hydrothermal conditions and in an organic solvent according to a method for producing an organically modified carbon material according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Hereinafter, the embodiment of the present invention will be described based on examples. In the method for producing an organically modified carbon material according to an embodiment of the present invention, the surface of the carbon material can be organically modified with an organic compound having one or more functional groups (excluding silicon compounds) in a reaction field of subcritical water, supercritical water, or a supercritical organic solvent. In addition, the surface of the carbon material may be subjected to an oxidation treatment simultaneously with or prior to the organic modification.

[0035] As examples, (1) carbon materials subjected to a surface oxidation treatment are shown in Examples 1 to 4, (2) carbon materials subjected to a surface oxidation treatment and organic modification are shown in Examples 5 to 11, and (3) carbon materials subjected to organic modification without surface oxidation treatment are shown in Examples 12 to 17. Examples 1 to 17 show the results obtained under hydrothermal conditions using subcritical water or supercritical water, and Examples 5, 10, 12 to 14, and 17 show the results obtained in a reaction field using a supercritical organic solvent.

[0036] In the following examples, raw materials were placed in a batch reactor, heated to the respective temperatures in an autoclave, and reacted to perform organic modification. Although pressure was not measured, it is empirically considered to be approximately 20 to 35 MPa. EXAMPLES

[0037] [Surface oxidation treatment - nano diamond] A surface oxidation treatment of nanodiamond was carried out under hydrothermal conditions using sub-critical or supercritical water. In the experiment, 2.5 mL of water and 0.02 g of powdered nanodiamond were placed in a reactor, and the treatment was carried out for 10 minutes at temperatures of 200°C, 250°C, 300°C, or 350°C. After the treatment, measurements were carried out using thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR). The unit of weight change rate in thermogravimetry is weight % (wt.%) (same below).

[0038] The results of the thermogravimetric analysis are shown in Figure 1(a), and the FTIR spectrum in Figure 1(b). For comparison, the results of untreated nanodiamonds are also shown (pure ND). As shown in Figure 1(a), the results of the thermogravimetric analysis showed that, under all temperature conditions, the weight of the nanodiamonds was reduced by about 1-3 wt.% up to 800°C compared to the untreated ones, which suggests that the hydrothermal treatment oxidizes the surface of the nanodiamonds, imparting functionality to them. Furthermore, as shown in Figure 1(b), after treatment, the FTIR spectrum at 1500cm -1 , 2900cm -1 , 3500cm -1 New peaks corresponding to CO, CH2, and OH were observed near the surface, suggesting that the surface of the nanodiamonds is oxidized. EXAMPLES

[0039] [Surface oxidation treatment - MWCNT - reaction with hydrogen peroxide] Surface oxidation treatment of multi-walled carbon nanotubes (MWCNTs) was carried out under hydrothermal conditions. In the experiment, 2.5 mL of 3% or 6% hydrogen peroxide solution (H2O2) and 0.02 g of multi-walled carbon nanotubes were placed in a reactor, and treatment was carried out for 10 or 20 minutes at temperatures of 200°C, 300°C, or 350°C. After treatment, measurements were carried out using a Fourier transform infrared spectrometer (FTIR).

[0040] The FTIR spectrum when 3% hydrogen peroxide solution was used is shown in Figure 2(a), and the FTIR spectrum when 6% hydrogen peroxide solution was used is shown in Figure 2(b). As shown in Figure 2(a), no new peak was observed in the 3% hydrogen peroxide solution, but as shown in Figure 2(b), a new peak was observed at 1500 cm in the 6% hydrogen peroxide solution. -1 , 2900cm -1 New peaks corresponding to CO and CH2 were observed in the vicinity, suggesting that the surface of the multi-walled carbon nanotubes is oxidized. EXAMPLES

[0041] [Surface oxidation treatment - MWCNT - reaction with water] Surface oxidation treatment of multi-walled carbon nanotubes (MWCNTs) was performed under hydrothermal conditions. In the experiment, 4 mL of water and 0.02 g of multi-walled carbon nanotubes were placed in a reactor, and the temperature was set to 250°C and treatment was performed for 30 minutes. After treatment, the multi-walled carbon nanotubes were collected by centrifugation and measured by thermogravimetry (TG).

[0042] The results of the thermogravimetric analysis are shown in Figure 3. For comparison, the results of untreated multi-walled carbon nanotubes (pure MWCNT) are also shown. As shown in Figure 3, the results of the thermogravimetric analysis showed a weight loss of about 14 wt.% up to 1000°C compared to the untreated one, which suggests that the surface of the multi-walled carbon nanotubes is oxidized by the hydrothermal treatment. EXAMPLES

[0043] [Surface oxidation treatment - graphene] Surface oxidation of graphene was performed under hydrothermal conditions. In the experiment, 2.5 mL of water and 0.02 g of graphene were placed in a reactor, and the temperature was set to 200°C, 250°C, 300°C, 350°C, or 400°C, and the treatment was performed for 30 minutes. After the treatment, measurements were performed using thermogravimetry (TG).

[0044] The results of the thermogravimetric analysis are shown in Figure 4. For comparison, the results of untreated graphene are also shown (pure GT). As shown in Figure 4, the results of the thermogravimetric analysis showed that, under all temperature conditions, the weight of the graphene was reduced by about 1 to 6 wt.% up to 1000°C compared to the untreated graphene, which suggests that the surface of the graphene was oxidized by the hydrothermal treatment. EXAMPLES

[0045] [Amino bond - reaction of MWCNT with hexylamine] Multi-walled carbon nanotubes (MWCNTs) were reacted with hexylamine under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.3 mL (2.2 mmol) of hexylamine were placed in a reactor, and the reaction was carried out for 10 minutes at temperatures of 300°C, 350°C, or 400°C. After the reaction, measurements were made using a Fourier transform infrared spectrometer (FTIR).

[0046] The FTIR spectrum for each reaction temperature is shown in Figure 5. As shown in Figure 5, when the reaction temperature was 400 °C, the peak at 1540 to 1650 cm -1 A peak was observed in the range of 100 to 150 nm, indicating the presence of CH2. From these experimental results, it is believed that the surface of the multi-walled carbon nanotubes was organically modified by the reaction with hexylamine.

[0047] In addition, the reaction temperature was set to 400°C, and the pH of the water was changed to 9.8, 10.6, or 11.3, but the other conditions were the same when the reaction experiment was carried out. The FTIR spectrum for each pH is shown in Figure 6. As shown in Figure 6, at each pH, ​​the FTIR spectrum of 1500 to 1710 cm -1 It is considered that the surface of the multi-walled carbon nanotube is organically modified by the reaction with hexylamine.

[0048] In addition, a reaction experiment was carried out under the same conditions using toluene or ethanol as an organic solvent instead of water. The FTIR spectrum at this time is shown in Figure 7. As shown in Figure 7, even when toluene or ethanol was used, the FTIR spectrum at 1500-1710 cm -1 It is considered that the surface of the multi-walled carbon nanotube is organically modified by the reaction with hexylamine. EXAMPLES

[0049] [Amino bond - Reaction of MWCNT with various amines] Multi-walled carbon nanotubes (MWCNTs) were mixed with nitric acid (HNO3), and while adding sulfuric acid (H2SO4), they were stirred by sonication to perform surface oxidation treatment. Sonication was performed at room temperature for 6 hours. After oxidation treatment, they were reacted with various types of amines under hydrothermal conditions. For the reaction with amines, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.3 mL of various amines were placed in a reactor, and the temperature was set to 350°C or 400°C and the reaction was performed for 20 minutes. After the reaction, measurements were performed using thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR). The amines used as modifiers were hexylamine, decylamine, dodecylamine, oleylamine, 6-aminohexanol, and p-aminophenol.

[0050] The results of thermogravimetric analysis using hexylamine, decylamine, dodecylamine, and oleylamine are shown in Figure 8. For comparison, the results of oxidation only (only oxidized) and reaction with hexylamine at 400°C for 20 minutes without oxidation (hexylamine without oxidized) are also shown. The results of thermogravimetric analysis for each amine are summarized in Table 1. Figure 9 shows the FTIR spectra when hexylamine, decylamine, and dodecylamine were used. Figure 10 shows micrographs of multi-walled carbon nanotubes after reaction with hexylamine, decylamine, and dodecylamine.

[0051] [Table 1]

[0052] As shown in FIG. 8 and Table 1, the results of the thermogravimetric analysis confirmed that, for all amines, the weight was reduced by about 6 to 11 wt.% up to 600°C compared to those not subjected to oxidation treatment. In addition, as shown in FIG. 9, for all amines, the weight was reduced by about 1500 to 1710 cm. -1 A peak was confirmed in the range of . From these results, it is believed that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with each amine. In addition, as shown in Figure 10, it can be confirmed that the multi-walled carbon nanotubes do not aggregate in the solvent (water) but are dispersed. This is believed to be due to the surface of the multi-walled carbon nanotubes being organically modified. EXAMPLES

[0053] [Bonding via N or O atoms - Reaction of MWCNT with aspartic acid] Multi-walled carbon nanotubes (MWCNTs) were reacted with aspartic acid under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.3 mL of aspartic acid were placed in a reactor, and the reaction was carried out at 200°C, 250°C, 300°C, or 350°C for 30 minutes, and at 200°C for 60 minutes. After the reaction, the obtained material was washed with ethanol, dried, and measured by thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR).

[0054] The results of the thermogravimetric analysis are shown in Figure 11(a), and the FTIR spectra when reacted at 200°C for 30 minutes are shown in Figures 11(b) and (c). As shown in Figure 11(a), the results of the thermogravimetric analysis confirmed that the weight was reduced by about 16 to 23 wt.% up to 1000°C under all conditions. In addition, as shown in Figures 11(b) and (c), a peak was confirmed in the range of 1200 to 1700 cm-1. From these results, it is believed that the surface of the multi-walled carbon nanotube was organically modified by the reaction with aspartic acid. EXAMPLES

[0055] [Ester bond - Reaction of MWCNT with 1-decanol] Multi-walled carbon nanotubes (MWCNTs) were mixed with nitric acid (HNO3), and while adding sulfuric acid (H2SO4), they were stirred by sonication to carry out a surface oxidation treatment. The sonication treatment was carried out at room temperature for 6 hours. After the oxidation treatment, the MWCNTs were reacted with 1-decanol under hydrothermal conditions. In the reaction with 1-decanol, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.3 mL of 1-decanol were placed in a reactor, and the reaction was carried out at a temperature of 300°C, 350°C, or 400°C for 10 or 20 minutes. After the reaction, measurements were carried out using thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR).

[0056] The results of the thermogravimetric analysis are shown in Fig. 12(a), and the FTIR spectra when reacted at 300°C and 350°C are shown in Fig. 12(b). For comparison, Fig. 12(b) also shows the results for multi-walled carbon nanotubes that were only oxidized.

[0057] As shown in FIG. 12(a), the results of the thermogravimetric analysis confirmed that the weight was reduced by about 15 to 25 wt.% up to 1000°C under all reaction conditions. -1 From these results, it is believed that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with 1-decanol. EXAMPLES

[0058] [Fridal craft reaction - reaction with t-BuOH] Multi-walled carbon nanotubes (MWCNTs) were reacted with tertiary butyl alcohol (t-BuOH) under hydrothermal conditions. In the experiment, the following reactors were placed in the reaction vessels: (1) 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 1.19 mL of t-BuOH (with water), (2) 0.02 g of multi-walled carbon nanotubes and 2.5 mL of t-BuOH (without water), and (3) for comparison, 2.5 mL of water and 0.02 g of multi-walled carbon nanotubes (pure MWCNTs; no t-BuOH). The reaction was carried out at 300°C for 30 minutes. After the reaction, measurements were performed using thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR).

[0059] The results of the thermogravimetric analysis are shown in Fig. 13(a), and the FTIR spectra (vertical axis is transmittance, horizontal axis is wavenumber) are shown in Fig. 13(b) to (g). As shown in Fig. 13(a), the results of the thermogravimetric analysis confirmed that the weight of the two samples containing t-BuOH was reduced by about 2 to 3 wt.% up to 800 °C, compared to the sample containing only water without t-BuOH. In addition, as shown in Fig. 13(b) to (g), the two samples containing t-BuOH (Figs. 13(b), (c), (f), (g)) showed a decrease in the FTIR spectrum from 1600 to 1800 cm -1 Peaks indicating the presence of esters or COOH were confirmed in the range. These results suggest that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with t-BuOH.

[0060] Next, (1) 0.02g of multi-walled carbon nanotubes and 2mmol of t-BuOH were placed in a reactor and reacted at 300℃ for 30 minutes, and (2) 0.02g of multi-walled carbon nanotubes were mixed with 2.5mL of 0.05M sulfuric acid (H2SO4) and stirred for 8 minutes by ultrasonic treatment to perform surface oxidation treatment, and the multi-walled carbon nanotubes after the oxidation treatment and 2mmol of t-BuOH were placed in a reactor and reacted at 300℃ for 30 minutes. After each reaction, the multi-walled carbon nanotubes were taken out of the reactor and immersed in hexane for a day and a night. After drying, they were measured by thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR).

[0061] The results of the thermogravimetric analysis are shown in Figure 14(a), and the FTIR spectrum is shown in Figure 14(b). As shown in Figure 14(a), the results of the thermogravimetric analysis confirmed that the weight was reduced by about 12 to 15 wt.% up to 800°C under all conditions. In addition, as shown in Figure 14(b), -1 From these results, it is considered that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with t-BuOH, regardless of whether the multi-walled carbon nanotubes are oxidized or not.

[0062] Next, (1) 0.02g of multi-walled carbon nanotubes, 2mmol of t-BuOH, and 2.5mL of 0.05M sulfuric acid were placed in a reactor, reacted at 300℃ for 30 minutes, and then immersed in hexane overnight. Thermogravimetric analysis (TG) and microscopic observation were performed on the samples. For comparison, (2) 0.02g of multi-walled carbon nanotubes, 2mmol of t-BuOH, and 2.5mL of 0.05M sulfuric acid were placed in hexane overnight (with t-BuOH), and (3) 0.02g of multi-walled carbon nanotubes and 2.5mL of 0.05M sulfuric acid were placed in hexane overnight (without t-BuOH). Thermogravimetric analysis (TG) was also performed on the samples.

[0063] The results of the thermogravimetric analysis are shown in Figure 15(a), and the micrographs are shown in Figures 15(b) and (c). As shown in Figure 15(a), it was confirmed that the sample reacted at 300°C for 30 minutes lost a larger amount of weight by about 5 to 6 wt.% up to 800°C compared to the other samples. This suggests that the surface of the multi-walled carbon nanotubes was organically modified by reacting with t-BuOH at high temperature and high pressure. In addition, as shown in Figures 15(b) and (c), it was confirmed that the multi-walled carbon nanotubes were dispersed in the solvent without agglomerating. This is believed to be due to the surface of the multi-walled carbon nanotubes being organically modified.

[0064] Next, 0.02g of multi-walled carbon nanotubes, 2mmol of t-BuOH, and 2.5mL of 0.05M sulfuric acid were placed in a reactor and reacted at 300℃ for 30 minutes, then immersed in hexane for 24 or 70 hours. After that, the tubes were washed with ethanol, dried at 60℃, and subjected to thermogravimetric analysis (TG) and Fourier transform infrared spectroscopy (FTIR).

[0065] The results of the thermogravimetric analysis are shown in Figure 16(a), and the FTIR spectrum (vertical axis is transmittance, horizontal axis is wave number) is shown in Figure 16(b) and (c). As shown in Figure 16(a), when the immersion time in hexane was 24 hours, the weight was reduced by about 9 wt.% up to 800 °C, and when it was 70 hours, the weight was reduced by about 15 wt.% up to 800 °C, and it was confirmed that the longer the immersion time in hexane, the greater the weight reduction. In addition, as shown in Figure 16(b) and (c), peaks indicating esters were observed in the range of 1100 to 1700 cm-1, and a clear peak was confirmed when the immersion time in hexane was 70 hours. From these results, it is considered that the longer the immersion time in hexane, the more the organic modification progresses. EXAMPLES

[0066] [Amino bond - reaction of BMAB with decylamine] Boron-modified acetylene black (BMAB) was reacted with decylamine under hydrothermal conditions. In the experiment, the reactor was charged with (1) 2.5 mL of water, 0.02 g of BMAB, and 0.3 mL of decylamine (with decylamine), and (2) for comparison, 2.5 mL of water and 0.02 g of BMAB (without decylamine), and the reaction was carried out at 400°C for 30 minutes. After the reaction, measurements were carried out by thermogravimetry (TG).

[0067] The results of the thermogravimetric analysis are shown in Figure 17. For comparison, the results of the thermogravimetric analysis of untreated BMAB (pure BMAB) are also shown in Figure 17. As shown in Figure 17, the results of the thermogravimetric analysis showed that the sample containing decylamine lost weight by about 2 wt.% up to 800°C compared to the sample containing only water without decylamine, which suggests that the surface of BMAB was organically modified by the reaction with decylamine.

[0068] Next, BMAB was subjected to surface oxidation treatment by ultrasonication in water, and then reacted with decylamine at 300°C for 30 minutes using hexane, ethanol, or toluene as an organic solvent. After the surface oxidation treatment, measurements were performed using a Fourier transform infrared spectrometer (FTIR), and after the reaction with decylamine, measurements were performed using thermogravimetry (TG) and FTIR.

[0069] The results of the thermogravimetric analysis are shown in Figure 18(a), and the FTIR spectra (vertical axis is transmittance, horizontal axis is wave number) are shown in Figures 18(b) and (c). As shown in Figure 18(a), the results of the thermogravimetric analysis confirmed that in all organic solvents, the weight was reduced by about 5 to 8 wt.% up to 800 °C. In addition, although this was not observed after the surface oxidation treatment in Figure 18(b), after the reaction with decylamine, as shown in Figure 18(c), a peak was observed in the range of 1100 to 1500 cm. -1 A peak indicating BOC or BO was confirmed in the range. These results suggest that the surface of BMAB was organically modified by reaction with decylamine.

[0070] Next, BMAB was mixed with 0.8M nitric acid (HNO3) for surface oxidation, and then reacted with decylamine at 300°C for 30 minutes using hexane, ethanol, or toluene as an organic solvent. After the reaction, measurements were performed using thermogravimetry (TG) and Fourier transform infrared spectroscopy (FTIR).

[0071] The results of the thermogravimetric analysis are shown in FIG. 19(a), and the FTIR spectra are shown in FIG. 19(b) to (d). For comparison, the results of the thermogravimetric analysis of (1) untreated BMAB (pure BMAB), (2) BMAB hydrothermally treated at 400°C for 30 minutes (in water), and (3) BMAB after surface oxidation treatment with HNO3 (only HNO3) are also shown in FIG. 19(a). As shown in FIG. 19(a), the results of the thermogravimetric analysis confirmed that in all organic solvents, the weight of BMAB was reduced by 15 wt.% or more up to 800°C compared to untreated BMAB and BMAB after hydrothermal treatment, and by about 2 to 13 wt.% compared to BMAB after surface oxidation treatment. In addition, as shown in FIG. 19(b) to (d), after the reaction with decylamine, the peaks of the FTIR spectra were increased from 1100 to 1500 cm. -1 A peak indicating BOC or BO was confirmed in the range. These results suggest that the surface of BMAB was organically modified by reaction with decylamine.

[0072] In addition, experiments were also performed using diamine instead of decylamine, and similar results were obtained. In addition, experiments were also performed using acetylene black (AB) instead of BMAB, and similar results were obtained. EXAMPLES

[0073] [Reaction of N-bonded MWCNT with N-bromosuccinimide] Multi-walled carbon nanotubes (MWCNTs) were reacted with N-bromosuccinimide (NBS) under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.35 g of NBS were placed in a reactor, and the mixture was stirred for 5 to 8 minutes by ultrasonic treatment (sonication), and then the temperature was raised to 200°C, 250°C, 300°C, 350°C, or 400°C and the mixture was reacted for 30 minutes. After the reaction, thermogravimetric analysis (TG) was performed. In addition, the reaction at 200°C was measured using a Fourier transform infrared spectrometer (FTIR) and energy dispersive X-ray analysis (EDX), and the reaction at 200°C and 250°C was observed under a microscope.

[0074] The results of the thermogravimetric analysis are shown in FIG. 20(a). For comparison, the results of the thermogravimetric analysis of untreated multi-walled carbon nanotubes (pure MWCNT) are also shown in FIG. 20(a). As shown in FIG. 20(a), the results of the thermogravimetric analysis show that at all reaction temperatures, the weight of the multi-walled carbon nanotubes is reduced by about 5 to 40 wt.% compared to the untreated multi-walled carbon nanotubes up to 1000°C, which suggests that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with NBS. In addition, experiments were also performed using single-walled carbon nanotubes (SWCNTs) instead of multi-walled carbon nanotubes, and similar thermogravimetric analysis results were obtained as for the multi-walled carbon nanotubes.

[0075] The FTIR spectrum (vertical axis is transmittance, horizontal axis is wave number) is shown in FIG. 20(b). For comparison, the FTIR spectrum of the multi-walled carbon nanotube reacted with NBS and treated with oleylamine is shown in FIG. 20(c). As shown in FIG. 20(b), a peak (position of the arrow in the figure) indicating a COOH group is observed in the range of 600 to 1700 cm-1, and it is considered that the surface of the multi-walled carbon nanotube is organically modified by the reaction with NBS. Also, as shown in FIG. 20(c), it was confirmed that the peak in the range of 600 to 1700 cm-1 observed in FIG. 20(b) disappears when the multi-walled carbon nanotube is treated with oleylamine. From this, it is considered that the organic substances such as COOH that modified the surface of the multi-walled carbon nanotube are removed by oleylamine.

[0076] The results of the EDX analysis are shown in FIG. 21(a). For comparison, the results of the EDX analysis of untreated multi-walled carbon nanotubes are shown in FIG. 21(b). As shown in FIG. 21(a), the EDX analysis confirmed the presence of Br on the surface of the multi-walled carbon nanotubes, and it is believed that the surface of the multi-walled carbon nanotubes has been organically modified. Furthermore, by comparing FIG. 21(a) with FIG. 21(b), it can be confirmed that the reaction with NBS caused peaks of not only Br but also other metal elements and oxides to appear. From this, it is believed that the surface of the multi-walled carbon nanotubes has been organically modified by the reaction with NBS.

[0077] A micrograph of the multi-walled carbon nanotubes after reaction with NBS is shown in Figure 22. As shown in Figure 22, it can be confirmed that the multi-walled carbon nanotubes after reaction with NBS do not aggregate but are dispersed in the solvent (water). This is believed to be due to the fact that the surfaces of the multi-walled carbon nanotubes are organically modified. EXAMPLES

[0078] [Carbon-carbon bond; Diels alder reaction - reaction with DMBD] Multi-walled carbon nanotubes (MWCNT), graphene, or single-walled carbon nanotubes (SWCNT) were reacted with 2,3-dimethyl-1,3-butadiene (DMBD) under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of each carbon material, and 200 μL of DMBD were placed in a reactor, and the reaction was carried out at a temperature of 300 °C for 30, 60, 90, or 120 minutes. After the reaction, measurements were performed using thermogravimetry (TG).

[0079] The results of thermogravimetric analysis of multi-walled carbon nanotubes, graphene (reaction time 60 min), and single-walled carbon nanotubes are shown in Figures 23(a) to 23(c), respectively. As shown in Figure 23(a), the weight of the multi-walled carbon nanotubes was reduced by about 15 to 25 wt.% up to 1000°C for all reaction times, suggesting that the surface of the multi-walled carbon nanotubes was organically modified by the reaction with DMBD. As shown in Figure 23(b), the weight of graphene (reaction time 60 min) was reduced by about 3 wt.% compared to that of the one not reacted with DMBD (pure GT), suggesting that the surface of graphene was organically modified by the reaction with DMBD. As shown in Figure 23(c), the weight of the single-walled carbon nanotubes was reduced by more than 40 wt.% up to 1000°C for all reaction times, suggesting that the surface of the single-walled carbon nanotubes was organically modified by the reaction with DMBD.

[0080] Next, toluene was used as the organic solvent instead of water, and the other treatment conditions were the same. The multi-walled carbon nanotubes were reacted with DMBD at 300°C for 30, 60, 90, or 120 minutes. After the reaction, measurements were performed by thermogravimetry (TG). The results of the thermogravimetry are shown in FIG. 24. As shown in FIG. 24, the weight decreased by about 14 to 20 wt.% up to 1000°C for each reaction time, which suggests that the surface of the multi-walled carbon nanotubes was organically modified by the reaction with DMBD.

[0081] To compare the case where water was used in Fig. 23(a) with the case where toluene, an organic solvent, was used in Fig. 24, the change in the weight loss rate (at 600°C) versus reaction time was calculated and shown in Fig. 25. As shown in Fig. 25, the weight loss rate is greater when water is used, which suggests that water is a better solvent. It can also be seen that in both cases, the weight loss rate is greatest when the reaction time is 30 minutes.

[0082] Next, single-walled carbon nanotubes (SWCNTs) were used, and under the same treatment conditions, the single-walled carbon nanotubes, water, and DMBD were reacted for 30 minutes at temperatures of 200, 250, 300, or 350°C. After the reaction, measurements were made by thermogravimetry (TG). The results of the thermogravimetry are shown in FIG. 26. As shown in FIG. 26, at each reaction temperature, the weight decreased by about 37 to 50 wt.% up to 1000°C, which suggests that the surface of the single-walled carbon nanotubes was organically modified by the reaction with DMBD. EXAMPLES

[0083] [π-π interaction - reaction of MWCNT with anthracene] Multi-walled carbon nanotubes (MWCNTs) were reacted with anthracene under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.178 g of anthracene were placed in a reactor, and the temperature was set to 200°C or 250°C, and the reaction was allowed to proceed for 30 minutes. After the reaction, the samples were washed four times with ethanol and once with acetone, and measurements were performed using thermogravimetry (TG). In addition, measurements were also performed using a Fourier transform infrared spectrometer (FTIR) for the samples reacted at 200°C.

[0084] The results of the thermogravimetric analysis are shown in Figure 27(a), and the FTIR spectrum is shown in Figure 27(b). As shown in Figure 27(a), the results of the thermogravimetric analysis confirmed that at all reaction temperatures, the weight was reduced by about 15 to 20 wt.% up to 1000°C. In addition, as shown in Figure 27(b), a peak was confirmed at around 2900 cm-1 after the reaction with anthracene. From these results, it is believed that the surface of the multi-walled carbon nanotube is organically modified by the reaction with anthracene.

[0085] Next, 2.5 mL of water or toluene or ethanol as an organic solvent, 0.02 g of multi-walled carbon nanotubes, and 0.178 g of anthracene were placed in a reactor, and the temperature was raised to 300°C and the mixture was reacted for 30 minutes. After the reaction, the mixture was cooled with cold water, washed with acetone, and dried overnight at 60°C. After drying, measurements were performed using thermogravimetric analysis (TG).

[0086] The results of the thermogravimetric analysis are shown in Figure 28. For comparison, the results of the thermogravimetric analysis of untreated multi-walled carbon nanotubes (pure MWCNT) are also shown in Figure 28. As shown in Figure 28, the results of the thermogravimetric analysis showed that at all reaction temperatures, the weight was reduced by about 11 to 15 wt.% up to 1000°C compared to the untreated one, suggesting that the surface of the multi-walled carbon nanotubes was organically modified by the reaction with anthracene. EXAMPLES

[0087] [π-π interaction - reaction of MWCNT with aminoanthracene] Multi-walled carbon nanotubes (MWCNTs) were reacted with aminoanthracene under hydrothermal conditions. In the experiment, 2.5 mL of water or toluene, 0.02 g of multi-walled carbon nanotubes, and 0.38 g of 2-aminoanthracene were placed in a reactor, and the reaction was carried out for 30 minutes at temperatures of 200°C, 250°C, 300°C, or 350°C. After the reaction, measurements were performed using thermogravimetry (TG). In addition, measurements were also performed using a Fourier transform infrared spectrometer (FTIR) for the cases in which water was used as the solvent.

[0088] The results of the thermogravimetric analysis when water was used as the solvent are shown in FIG. 29(a), and the FTIR spectrum (vertical axis is transmittance, horizontal axis is wave number) is shown in FIG. 29(b)-(e). For comparison, the results of the thermogravimetric analysis of untreated multi-walled carbon nanotubes are also shown in FIG. 29(a) (pure MWCNT). As shown in FIG. 29(a), the results of the thermogravimetric analysis confirmed that the weight of the untreated multi-walled carbon nanotubes was reduced by about 2-4 wt.% up to 800°C at all reaction temperatures compared to the untreated multi-walled carbon nanotubes. In addition, as shown in FIG. 29(c)-(e), a peak indicating CH (arrow in the figure) was confirmed in the range of 750-900 cm-1 after the reaction with aminoanthracene at 250-350°C. From these results, it is considered that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with aminoanthracene.

[0089] Moreover, the results of thermogravimetric analysis when toluene was used as the organic solvent are shown in Figure 30. As shown in Figure 30, the results of thermogravimetric analysis showed that the weight was reduced by about 5 to 8 wt.% up to 800°C at all reaction temperatures, which suggests that the surface of the multi-walled carbon nanotube was organically modified by the reaction with aminoanthracene. EXAMPLES

[0090] [π-π interaction - reaction of MWCNT with naphthalene] Multi-walled carbon nanotubes (MWCNTs) were reacted with naphthalene under hydrothermal conditions. In the experiment, 2.5 mL of water, 0.02 g of multi-walled carbon nanotubes, and 0.15 g of naphthalene were placed in a reactor, and the reaction was carried out for 30 minutes at temperatures of 200°C, 250°C, 300°C, or 350°C. After the reaction, measurements were performed using thermogravimetry (TG).

[0091] The results of the thermogravimetric analysis are shown in Figure 31. For comparison, the results of the thermogravimetric analysis of untreated multi-walled carbon nanotubes are also shown (pure MWCNT). As shown in Figure 31, the results of the thermogravimetric analysis show that at all reaction temperatures, the weight of the multi-walled carbon nanotubes is reduced by about 6 to 15 wt.% up to 1000°C compared to the untreated multi-walled carbon nanotubes, which suggests that the surface of the multi-walled carbon nanotubes is organically modified by the reaction with naphthalene. EXAMPLES

[0092] [π-π interaction - reaction of MWCNT with benzyl alcohol] Multi-walled carbon nanotubes (MWCNTs) were subjected to surface oxidation treatment by stirring with sonication while adding sulfuric acid (H2SO4). Here, 0.02g of multi-walled carbon nanotubes was placed in 2.5mL (0.05M) of sulfuric acid and sonicated for 8 minutes. After oxidation treatment, they were reacted with benzyl alcohol under hydrothermal conditions. Here, the multi-walled carbon nanotubes after oxidation treatment and 2mmol of benzyl alcohol were placed in a reactor and reacted for 30 minutes at temperatures of 200℃, 250℃, 300℃, 350℃ or 400℃. After the reaction, measurements were made by thermogravimetry (TG). In addition, measurements were made by Fourier transform infrared spectroscopy (FTIR) for those reacted at 300℃.

[0093] The results of the thermogravimetric analysis are shown in Figure 32(a). From the results, the relationship between the weight change rate at around 800°C and the reaction temperature was calculated, and is shown in Figure 32(b). For comparison, the results of the thermogravimetric analysis of untreated multi-walled carbon nanotubes (pure MWCNT) and those reacted at room temperature (RT) are also shown in Figure 32(a). FTIR spectra (vertical axis is transmittance, horizontal axis is wavenumber) are shown in Figures 33(a) and (b), and micrographs of the multi-walled carbon nanotubes after the reaction are shown in Figures 33(c) and (d). Experiments were also conducted using single-walled carbon nanotubes (SWCNT) instead of multi-walled carbon nanotubes, and similar results were obtained as with the multi-walled carbon nanotubes.

[0094] As shown in Figure 32(a), the results of thermogravimetric analysis showed that at all reaction temperatures up to 1000°C, the weight of the multi-walled carbon nanotubes was reduced by about 12-24 wt.% compared to untreated multi-walled carbon nanotubes and by about 5-17 wt.% compared to those reacted at room temperature, suggesting that the surface of the multi-walled carbon nanotubes was organically modified by the reaction with benzyl alcohol. Also, as shown in Figure 32(b), it was confirmed that the weight reduction was greatest when the reaction was carried out at 300°C.

[0095] As shown in Figures 33(a) and (b), a peak indicating an ether (-COC-) bond is observed in the range of 600 to 1200 cm-1, and it is believed that the surface of the multi-walled carbon nanotube is organically modified by the reaction with benzyl alcohol. As shown in Figures 33(c) and (d), it can be confirmed that the multi-walled carbon nanotube does not aggregate in the solvent (sulfuric acid) but is dispersed. This is believed to be due to the surface of the multi-walled carbon nanotube being organically modified. EXAMPLES

[0096] [π-π interaction - reaction of MWCNT with naphthalenedicarboxylic acid] Multi-walled carbon nanotubes (MWCNTs) were reacted with 2,6-naphthalene dicarboxylic acid (NDCA). In the experiment, 2.5 mL of water or toluene or ethanol as an organic solvent, 0.02 g of multi-walled carbon nanotubes, and 0.1 g of NDCA were placed in a reactor, and the temperature was set to 300°C and the reaction was carried out for 30 minutes. After the reaction, the tubes were cooled with cold water, washed with 1 M ammonia water (NH4OH), and dried overnight at 60°C. After drying, measurements were carried out using thermogravimetric analysis (TG).

[0097] The results of the thermogravimetric analysis are shown in Figure 34. For comparison, the results of untreated multi-walled carbon nanotubes (pure MWCNT) are also shown in Figure 34. As shown in Figure 34, the results of the thermogravimetric analysis showed that in all solvents, the weight was reduced by about 10 to 14 wt.% up to 800°C compared to the untreated one, which suggests that the surface of the multi-walled carbon nanotube was organically modified by the reaction with NDCA.

Claims

1. a surface oxidation step of oxidizing a carbon surface of the carbon material with an oxidizing agent; an organic modification step of adding an organic compound having one or more functional groups (excluding silicon compounds) and a solvent to the surface-oxidized carbon material after the surface oxidation step, and organically modifying the surface-oxidized surface with the organic compound in a reaction field of subcritical water, supercritical water, or supercritical organic solvent; The present invention relates to a method for producing a carbon material having an organically modified carbon surface, comprising the steps of:

2. The method of claim 1 , wherein the oxidizing agent comprises at least one of hydrogen peroxide, oxygen gas, nitric acid, and sulfuric acid.

3. The method according to claim 1 or 2, wherein the surface oxidation treatment is carried out while performing ultrasonic treatment.

4. 3. The method according to claim 1, wherein the surface oxidation treatment is carried out in a reaction field of subcritical water, supercritical water, or a supercritical organic solvent.

5. The method according to claim 1 , wherein the organic modification step is a step of organically modifying the surface that has been oxidized by reacting the surface with the organic compound.

6. 6. The method according to claim 1, wherein the organic modification step is a step of organically modifying the surface-oxidized surface with the organic compound through an ether bond, an ester bond, a bond via an N atom including an amino bond or an amide bond, a bond via an S atom, a bond via a P atom, a bond via a B atom, a phosphate ester bond, a borate ester bond, a phosphorous acid bond, a phosphonic acid bond, a phosphonous acid bond, a phosphinic acid bond, or a phosphinous acid bond.

7. The method according to any one of claims 1 to 6, wherein the temperature of the reaction field is 200°C or higher and lower than 450°C.

8. a dehydration condensation product obtained by organically modifying a carbon surface of a carbon material (excluding diamond) with an organic compound (excluding silicon compounds) through an ether bond, an ester bond, a bond via an N atom including an amino bond or an amide bond, a bond via an S atom (excluding those having an amine group), a bond via a P atom, a phosphate ester bond, a phosphorous bond, a phosphonic acid bond, a phosphonous acid bond, a phosphinic acid bond, or a phosphinous acid bond; A carbon material having an organically modified carbon surface, wherein the weight ratio of the molecules that organically modify the carbon surface is 6 wt. % or more.

Citation Information

Patent Citations

  • JP1974048676A

  • Polymerizable nano-diamond and method for producing the same

    JP2011132117A

  • Dielectric material

    JP2012188476A

  • Production method of organically modified carbon material, and organically modified carbon material

    JP2017081764A

  • Method and apparatus for preparing functionalized graphene, and functionalized graphene

    WO2015076565A1